Review: Approaches to Visual-motor Control in Baseball Batting. Issue 7 (July 2021) - Gray, Rob
Abstract : SIGNIFICANCE: This review evaluates model-based online approaches to visual-motor control in baseball batting in light of research studies on this topic. Throughout the history of research on baseball batting, there has been a presumptive winner in terms of how visual-motor control occurs for this complex skill. Because of the severe time constraints and the short duration of the action, it has been assumed that a baseball swing must involve model-based control. That is, hitting involves using an open-loop, pre-programmed movement that is parameterized based on situational probabilities, advance cues from the pitcher's delivery, and information early in the ball flight, which are used by an internal model to predict the future location of the ball. In this review, the author contrasts two variants of this type of model-based control (a 3D world model and spatial memory of trajectories) with an online control approach in which the batter uses only currently available perceptual information to control the swing prospectively via information-movement coupling. It is shown that the assumed necessity of predictive control in baseball batting is based on too narrow of a conception of online control. Although work still needs to be done to elucidate the specifics of the control, it is argued here that online control provides an account of visual-motor control in baseball batting that is both more parsimonious and more consistent with published research findings.